Advertisement of beauty products using social media influencers (SMIs) and customers’ trust in Shah Alam / Izzati ‘Aliah Zaidi and Wardatul Hayat Adnan - Zaidi, Izzati ‘Aliah; Adnan, Wardatul Hayat (Universiti Teknologi MARA, 2021)
Internet and social media platforms speed up the digital growth of advertisements in our societies to promote brands and products. The upsurge advertisement using social media influencers (SMIs) has attracted female millennials to purchase beauty products on social media platforms. However, there are still lack of research conducted to examine the influence of advertisement using social media influencers (SMIs) towards the customers’ trust on beauty products although SMIs endorsement has been studied over the years. It was revealed in past research that trust has the strongest influence on customers’ purchase intention. Therefore, this study aims to identify the influence of advertisement using social media influencers (SMIs) towards customers’ trust on beauty products amongst social media users in Shah Alam. This study employed a quantitative study where 50 respondents amongst social media users in Shah Alam participated. Findings of this study revealed that influencer credibility and electronic Word of Mouth (eWOM) significantly influence the customers’ trust in beauty products in Shah Alam.